Î²-cyfluthrin and imidacloprid ready mix formulation against major insects pests of soybean - Punithavalli, M S; Sharma1, A N (Indian Journal of Plant Protection, 2020)
A ready mix formulation Solomon 300 OD (beta" - "cyfluthrin 9% + imidacloprid 21% - 300 OD) was evaluated against semilooper complex comprising of Chrysodeixis acuta, Diachrysia orichalcea and Gesonia gemma and internal feeder girdle beetle, Obereopsis brevis in soybean under field conditions. Three doses of Solomon 300 OD @ 75, 90 and 105 g a.i./ha along with three check insecticides viz., beta-cyfluthrin 2.5 % SC @ 31.5 g a.i./ ha, imidacloprid 200 SL @ 73.5 g a.i./ha and triazophos 40 EC 250 g a.i./ha were tested at crop flowering stage as foliar spray. Solomon 300 OD @ 105 g a.i./ha was highly effective for semiloopers and provided protection beyond 10 days after treatment. Besides, the check insecticide, triazophos 40 EC 250 g a.i./ha was also equally effective in reducing semiloopers larval populations in soybean. However, none of the three doses of Solomon 300 OD could be found effective against girdle beetle in all the seasons. There were no considerable differences in yield of soybean at doses of Solomon 300 OD @ 75, 90 and 105 g a.i./ha and no phytotoxic effects were observed on soybean foliage.